Mechanisms for supporting and accompanying start-ups in Algeria - Kheira, Nouari; Safia, Amir (International journal of economic perspectives, 2024)
The study aimed to explore ways to support and guide start-ups in Algeria by examining strategies that could enhance this sector, utilizing a descriptive analytical approach. The findings suggest that building and growing start-ups necessitate a comprehensive, integrated framework that encourages positive interactions between personal attributes and social and economic factors. This framework should promote a supportive culture and education system, a conducive institutional environment, a favorable business climate, and facilitate access to funding from a variety of innovative sources. The Algerian government is showing increased interest in start-ups by developing support and guidance mechanisms for young entrepreneurs, project leaders, and innovators, despite the existing challenges and difficulties within the start-up ecosystem.